Pharmacological effects and therapeutic potential of natural compounds in neuropsychiatric disorders: An update - Asgharian, Parina; Quispe, Cristina; Herrera-Bravo, Jesús; Sabernavaei, Mahsa; Hosseini, Kamran; Forouhandeh, Haleh; Ebrahimi, Tahereh; Sharafi-Badr, Paria; Tarhriz, Vahideh; Soofiyani, Saiedeh Razi; Helon, Paweł; Rajkovic, Jovana; et al. (Frontiers in Pharmacology, 2022)
Neuropsychiatric diseases are a group of disorders that cause significant morbidity and disability. The symptoms of psychiatric disorders include anxiety, depression, eating disorders, autism spectrum disorders, attention-deficit/hyperactivity disorder, and conduct disorder. Various medicinal plants are frequently used as therapeutics in traditional medicine in different parts of the world. Nowadays, using medicinal plants as an alternative medication has been considered due to their biological safety. Despite the wide range of medications, many patients are unable to tolerate the side effects and eventually lose their response. By considering the therapeutic advantages of medicinal plants in the case of side effects, patients may prefer to use them instead of chemical drugs. Today, the use of medicinal plants in traditional medicine is diverse and increasing, and these plants are a precious heritage for humanity. Investigation about traditional medicine continues, and several studies have indicated the basic pharmacology and clinical efficacy of herbal medicine. In this article, we discuss five of the most important and common psychiatric illnesses investigated in various studies along with conventional therapies and their pharmacological therapies. For this comprehensive review, data were obtained from electronic databases such as MedLine / PubMed, Science Direct, Web of Science, EMBASE, DynaMed Plus, ScienceDirect, TRIP database. Preclinical pharmacology studies have confirmed that some bioactive compounds may have beneficial therapeutic effects in some common psychiatric disorders. The mechanisms of action of the analyzed biocompounds are presented in detail. The bioactive compounds analyzed in this review are promising phytochemicals for adjuvant and complementary drug candidates in the pharmacotherapy of neuropsychiatric diseases. Future clinical studies are needed to accelerate the use of natural compounds in the management of these diseases.